FORMULATION AND EVALUATION OF HERBAL CAPSULE CONTAINING CURCUMA MANGGA VALETON and ZIJP. EXTRACT AND ITS IMMUNOSTIMULATORY EFFECTS - YUANDANI; LAILA, LIA; NUGRAHA, SONY EKA; HASIBUAN, WAHYU ARNIDA; NASUTION, RIFDA YUSRINA; SATRIA, DENNY (International Journal of Applied Pharmaceutics, 2023)
Objective: The present study was carried out to formulate and evaluate C. mangga extract as granule mass in a capsule dosage form as well as investigate its immunostimulatory effects. Methods: The granule mass was evaluated for its bulk density, tapped density, Carr’s index, Hausner ratio, angle of repose, and flow ability. Meanwhile, capsule weight and disintegration time were determined to evaluate the C. mangga capsule. The immunostimulatory effects of extract in capsule dosage form were investigated by measuring delayed-type hypersensitivity (DTH) response and IgG production. There were six formula prepared (F1-F6). Formula F1-F6 were vary according to the component of adsorbent (Corn starch/polyvinyl pyrrolidone) and filler (maltodextrin/Avicel/lactose) to obtain the optimum formula. Results: The granule mass of all formula had a good flow ability and free-flowing properties according to the Carr’s index (10.26±3.38 to 17.54±1.60) and flowing time (1.05±0.05 to 1.60±0.08 seconds). Of all the capsule formula, F2 capsule containing dry extract of C. mangga with Avicel as the filler met the standard requirement in terms of disintegration time (2.15±0.76 min) and weight uniformity (the deviation was below than 7.5%). The capsule of C. mangga extract enhanced the paw thickness as compared to those of the negative control (P<0.05). The level of Immunoglobulin G (IgG) was also increased after treatment with the capsule of C. mangga extract. Conclusion: The results suggest that the capsule of C. mangga extract has immunostimulatory effects, emphasizing its potential to be used for the treatment of infectious and immunodeficiency diseases.